Mutations in the Polycomb Group Gene polyhomeotic Lead to Epithelial Instability in both the Ovary and Wing Imaginal Disc in Drosophila. - Gandille, P.; Narbonne-Reveau, K.; Boissonneau, E.; Randsholt, N.; Busson, D.; Pret, A.M. (PLoS ONE, 2010)
Most human cancers originate from epithelial tissues and cell polarity and adhesion defects can lead to metastasis. The Polycomb-Group of chromatin factors were first characterized in Drosophila as repressors of homeotic genes during development, while studies in mammals indicate a conserved role in body plan organization, as well as an implication in other processes such as stem cell maintenance, cell proliferation, and tumorigenesis. We have analyzed the function of the Drosophila Polycomb-Group gene polyhomeotic in epithelial cells of two different organs, the ovary and the wing imaginal disc.Clonal analysis of loss and gain of function of polyhomeotic resulted in segregation between mutant and wild-type cells in both the follicular and wing imaginal disc epithelia, without excessive cell proliferation. Both basal and apical expulsion of mutant cells was observed, the former characterized by specific reorganization of cell adhesion and polarity proteins, the latter by complete cytoplasmic diffusion of these proteins. Among several candidate target genes tested, only the homeotic gene Abdominal-B was a target of PH in both ovarian and wing disc cells. Although overexpression of Abdominal-B was sufficient to cause cell segregation in the wing disc, epistatic analysis indicated that the presence of Abdominal-B is not necessary for expulsion of polyhomeotic mutant epithelial cells suggesting that additional polyhomeotic targets are implicated in this phenomenon.Our results indicate that polyhomeotic mutations have a direct effect on epithelial integrity that can be uncoupled from overproliferation. We show that cells in an epithelium expressing different levels of polyhomeotic sort out indicating differential adhesive properties between the cell populations. Interestingly, we found distinct modalities between apical and basal expulsion of ph mutant cells and further studies of this phenomenon should allow parallels to be made with the modified adhesive and polarity properties of different types of epithelial tumors.